THE ROLE OF FEED FORWARD CONTROL OF LEADERSHIP AND K3 (OCCUPATIONAL HEALTH AND SAFETY) ON PREVENTIVE DISCIPLINE (STUDIESCASE OF EMPLOYEES OF PT. BARKAH JAYA MANDIRI SUKABUMI) - Nabila Maulidina; Kokom Komariah; Resa Nurmala (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research investigates the influence of leadership's feed-forward control and Occupational Health and Safety (K3) on preventative discipline among employees at PT. Barkah Jaya Mandiri Sukabumi. Quantitative methods with an associative approach were employed to analyze the relationships between variables. The results indicated that while both feed-forward control and K3 independently contribute to preventative discipline, K3 has a more significant impact. Simultaneously, the combination of feed-forward control and K3 creates a safer work environment and reinforces employee adherence to safety standards. This study highlights the importance of integrating proactive leadership with robust safety measures to cultivate a culture of preventative discipline in high-risk industries.